The 16th Conference of the Parties to the Convention on Biological Diversity adopts benefit-sharing rules for digital sequence information using Bioversity–CIAT-led CGIAR contributions - Halewood, Michael; Lopez Noriega, Isabel; Chiarolla, Claudio; Rouard, Mathieu (2025)
The 16th Conference of the Parties to the Convention on Biological Diversity adopted new rules for payments to, and disbursements from, an international fund, for benefit sharing from the use of digital sequence information. The decision excluded elements that CGIAR successfully lobbied against, which would have undermined agricultural research for development, following CGIAR objections. CGIAR, led by the genetic resources Policy team of the Alliance of Bioversity International and CIAT, played a crucial role, providing scientific evidence through written submissions, side events, bilateral meetings, and participation in negotiations.